(untitled) (International Journal of Studies in Nursing, 2020)
Background: The incidence of workplace violence has continued to occupy a significant place in healthcare at a rate nearly double that in other industries. Those providing direct bedside care are among the most vulnerable to violence, including nursing students. Many students report experiencing verbal or physical aggression prior to graduating from nursing school. Purpose: The purpose of this quantitative prospective experimental study was to measure the level of self-efficacy of nursing students’ verbal de-escalation skills before and after verbal de-escalation training, to see if the training made a measurable effect on the level of self-efficacy. Method: Seventeen nursing students in their psychiatric-mental health course rotation completed a pre- and post-intervention survey based on Thackrey’s Confidence in Coping with Patient Aggression scale (1987) to measure self-efficacy. The intervention included up to 90 minutes of interactive verbal de-escalation training. Result: A statistically significant increase in self-efficacy scores was noted from pre-intervention (M = 39, SD =